Scots pine – panmixia and the elusive signal of genetic adaptation - Bruxaux, Jade; Zhao, Wei; Hall, David; Curtu, Alexandru Lucian; Androsiuk, Piotr; Drouzas, Andreas D.; Gailing, Oliver; Konrad, Heino; Sullivan, Alexis R.; Semerikov, Vladimir; Wang, Xiao‐Ru (Wiley, 2024)
Summary